Fiqh Analysis For The Role Of Father In Child Education Based On Interpretation Of Tafseer Al-Munir Surah Luqman Verses 12-19 - Afthon Yazid (Intiqad: Jurnal Agama dan Pendidikan Islam, 2023)
A father has a very important role in the educational process of the child. Aspects of education can be imitated from Sura Luqman verses 12-19 which include tawhid education, worship and morals. Surah Luqman verses 12-19 can be studied in terms of fiqh so that the law is known from the aspect of education taught. This study aims to describe a fiqh analysis related to the role of the father in the education of children based on Tafseer Al-Munir Surah Luqman verses 12-19. This research is a type of literature research where researchers conduct studies on different reference sources. The results of the study were analysed descriptively. The results of the study are based on the analysis of fiqh Tafseer Al-Munir surah Luqman verses 12-19 that the fiqh laws can be taken to include; its haram to associate God with others; its haram to be arrogant, to walk arrogantly and even to say loudly or shout; obligatory filial piety to parents except in terms of mischief; and sunnah to pray for parents after every prayer.